The Incidence of V˙O2 plateau at V˙O2max in a Cardiac-Diseased Population - Nolan, P. B.; Maddison, R.; Dalleck, L. (International Journal of Sports Medicine, 2014)
We sought to determine the incidence of V˙O2 plateau at V˙O2max in a cardiovascular-diseased (CVD) population using 4 different sampling intervals (15-breath moving average, 15 s, 30 s, and 60 s) and 3 different V˙O2 plateau criteria (≤50 mL · min−1, ≤80 mL · min−1, and ≤150 mL · min−1). A total of 69 people (62±10 yrs.) with recently diagnosed CVD performed a maximal exercise test (10:07±2:24 min) on a treadmill. The test was classified as maximal (n=57, 2 430±605 mL · min−1) if self-terminated due to fatigue or classified as symptom-limited (n=12, 1 683±438 mL · min−1) if symptoms presented. Chi-square analysis revealed a significant (p<0.05) effect of sampling interval on incidence of V˙O2 plateau at V˙O2max across all 3 V˙O2 plateau criteria. The sampling interval had an increasingly stronger influence on the incidence of V˙O2 plateau at V˙O2max with smaller criterion thresholds as evidenced by the Cramer’s V statistics: [≤50 mL · min−1 (Cramer’s V=0.548, p<0.05], ≤80 mL · min−1 [Cramer’s V=0.489, p<0.05], ≤150 mL · min−1 [Cramer’s V=0.214, p<0.05]. Incidence of V˙O2 plateau at V˙O2max in CVD individuals is significantly influenced by the sampling interval applied. Based on our findings we recommend a15 breath moving average and V˙O2 plateau criterion of ≤50 mL · min−1.
Keywords: exercise testing; cardiovascular disease; oxygen plateau